Analysist Of Website Quality Impact on Users Satisfaction With WebQual Method at Hangtuah University Surabaya - Saputra, Taufan Oki; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Hang tuah university surabaya has an official website, click at www.hangtuah.ac.id which facilitates a lot of information that can be accessed by the users.The website contains such as the profil of the college, the bureau, research foundation and community services, technical implement unit (upt), faculty's information, students activity, UHT facility, regulation, scholarship information, and job vacancy.On this research, we do some analysis of the impact of services quality, scholarship information and foundation at website of hang tuang university surabaya about users' satisfaction based on the least user and visitor perception using webqual method. We collect data by giving online and offline questionnaire. The result of questionnaire is analysed based on webqual's indication. Then the questionnaire data result is tested its validity, reliability, classical assumption testing as a condition of linear regression testing.Based on the research that has been done so we conclude that the usage's quality (usability), the information quality and the interaction quality have the significant positive impact on users' satisfaction. The impact is about 67,6%. Key Words : Website Service Quality, Users Satisfaction, Linear Regression.